Palladium(II)/N, N-disubstituted-N′-acylthioureas complexes as anti-Mycobacterium tuberculosis and anti-Trypanosoma cruzi agents. (16th August 2017) - Plutín, Ana M.; Alvarez, Anislay; Mocelo, Raúl; Ramos, Raúl; Castellano, Eduardo E.; da Silva, Monize M.; Villarreal, Wilmer; Pavan, Fernando R.; Meira, Cássio Santana; Filho, José Simão Rodrigues; Moreira, Diogo Rodrigo M.; Soares, Milena Botelho P.; et al.
Graphical abstract: New complexes of Pd(II) with N, N -disubstituted- N ′-acylthioureas, with general formula [Pd(dppf)( N, N -disubstituted- N ′-acylthioureato-k 2 O, S)]PF6, (dppf = 1, 1- bis(diphenylphosphine)ferrocene) were prepared and characterized by elemental analysis, spectroscopic techniques, and by X-ray crystallography. The structures of complexes show that the ligands are coordinated to the metal through sulfur and oxygen atoms, forming distorted square-planar geometries. The complexes have shown antibacterial activity against anti- M. tuberculosis H37Rv ATCC 27294. Also, the complexes exhibited good antiparasitic activity against T. cruzi, while the metal-free thiourea did not. Abstract: The new complexes of Pd(II) with N, N -disubstituted- N ′-acylthioureas:[(1 ) [Pd(dppf)( N, N -dimethyl- N ′-benzoylthioureato-k 2 O, S)]PF6, (2 ) [Pd(dppf)( N, N -diethyl- N ′-benzoylthioureato-k 2 O, S)]PF6, (3 ) [Pd(dppf)( N, N -dibuthyl- N ′-benzoylthioureato-k 2 O, S)]PF6, (4 ) [Pd(dppf)( N, N -diphenyl- N ′-benzoylthioureato-k 2 O, S)]PF6, (5 ) [Pd(dppf)( N, N -diethyl- N ′-furoylthioureato-k 2 O, S)]PF6, (6 ) [Pd(dppf)( N, N -diphenyl- N ′-furoylthioureato-k 2 O, S)]PF6, (7 ) [Pd(dppf)( N, N -dimethyl-N′- thiophenylthioureato-k 2 O, S)]PF6, and (8 ) [Pd(dppf)( N, N -diphenyl-N′-thiophenylthioureato-k 2 O, S)]PF6, were prepared and characterized by elemental analysis, and spectroscopic techniques. The structures of complexes (2 ), (3 ), (5 ), (6 ) and (8 ) had their structures determined by X-ray crystallography, confirming the coordination of the ligands with the metal through sulfur and oxygen atoms, forming distorted square-planar geometries. These complexes have shown antibacterial activity against anti- Mycobacterium tuberculosis H37Rv ATCC 27294. The complexes exhibited antiparasitic activity against Trypanosoma cruzi, while the metal-free thioureas did not. The results demonstrated that the compounds described here can be considered as promising anti- Mycobacterium tuberculosis and anti- T. cruzi agents, since in both cases their in vitro activity were better than reference drugs available for the treatment of both diseases.